THE ROLE OF NATIONAL INSIGHTS AND TASTE OF NATIONALISM: PREVENTION OF RADICALISME FOR MIDDLE SCHOOL STUDENTS IN BOGOR - Iramdan Iramdan (Peneliti.net, 2019)
Nationality insight is also known as a guideline which is still a normative . Nationality insight is also known as a guideline which is still a normative philosophy. As an embodiment of the sense and national spirit that gave birth to the Indonesian nation. However, the situation and atmosphere of the environment that continues to change in line with the development process of the life of the nation from time to time